2016
DOI: 10.3141/2573-01
|View full text |Cite
|
Sign up to set email alerts
|

Using Parametric Modeling to Estimate Highway Construction Contract Time

Abstract: Federal regulations require that state transportation agencies have written procedures for setting the construction contract time for highway projects. Since the institution of those regulations, state agencies have used a variety of methods to estimate and set contract time. FHWA recommends the use of methods based on production rate and activity precedence and logic in this process. For years, the Kentucky Transportation Cabinet used a system based around these requirements and recommendations only to find t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…The present paper, on the other hand, explores a model that does not control for size and location, but is still able to achieve more accurate results. The increased accuracy can be attributed to the use of charge days to measure project duration versus the use of calendar days as used in previous research [3]). Another interesting finding is that the present research found that Terrain has no significant effect on project durations, even when some researchers have previously found that Terrain is a driver of production rates (5), which can be tied to project durations.…”
Section: Conclusion and Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…The present paper, on the other hand, explores a model that does not control for size and location, but is still able to achieve more accurate results. The increased accuracy can be attributed to the use of charge days to measure project duration versus the use of calendar days as used in previous research [3]). Another interesting finding is that the present research found that Terrain has no significant effect on project durations, even when some researchers have previously found that Terrain is a driver of production rates (5), which can be tied to project durations.…”
Section: Conclusion and Discussionmentioning
confidence: 98%
“…As a result, this research’s effort is focused on determining which are the most significant variables when trying to determine project durations to ease the estimation of project durations. A better understanding of such relationships will help facilitate a more accurate estimate of contract times, which is a key step in determining contract duration ( 3 ). The current research aims to expand on those models created by Zhai et al ( 3 ) by incorporating new project characteristics into parametric models that have not been considered in prior research.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations